Leishmania infantum-Derived Glycoinositolphospholipids in the Immunodiagnosis of Subclinically Infected Dogs - Sampaio, Julia Ramos; Soares, Rodrigo Pedro; Barral, Thiago Doria; Passos, Gabriela Porfirio; Fonseca, Maisa Santos; Meyer, Roberto; Barrouin-Melo, Stella Maria; Portela, Ricardo Wagner (Frontiers in Veterinary Science, 2021)
Lipophosphoglycan (LPG), when used as an ELISA target, confers high specificity and sensitivity to the detection of Leishmania infantum antibodies in dogs. Glycoconjugates are economically viable because the yield is very high after extraction/purification. In addition, they are very stable, which allows their use in point-of-care testing without special storage conditions. During the glycoconjugate extraction, a glycoinositolphospholipid (GIPL)-enriched fraction is obtained in similar quantities as LPG. Since GIPLs can be extracted from the same parasite pellet as LPGs, this work aimed to evaluate the immune recognition of GIPLs by Leishmania infantum-infected dogs and its use for canine leishmaniasis (CanL) immunodiagnosis. Like LPG, GIPLs were recognized by sera from L. infantum-infected dogs, but with less sensitivity (83.8%). However, 80% (16/20) of subclinically infected dogs were detected as positive in the assay. Different from LPG, the GIPL-based assay achieved a lower specificity (73.7%) and cross-reactions occurred with T. cruzi and L. braziliensis-infected dogs. Although GIPLs exhibited a similar performance to LPG for subclinically L. infantum-infected dogs, the occurrence of cross-reactivities with other protozoa and a lower sensitivity hinders its use for an immunodiagnostic test. In places where those diseases do not co-exist such as in the Mediterranean region, its use for subclinically dogs could be an alternative.